Analisis Preferensi dan Sikap Konsumen dalam Membeli Daging Ayam Lokal di Pasar Tradisional Kota Bandung - Pahlevi, Muhammad Shah Reza; Herlina, Linda; Nurlina, Lilis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The livestock industry has great potential in Indonesia, especially the local chicken industry. West Java Province has a large local chicken population, driven by the increasing consumption of local chicken meat which is considered to have a unique flavour. Consumers tend to buy local chicken meat in traditional markets and consider product attributes to suit their preferences. This study aims to determine the attributes that are the main considerations of consumers, as well as their preferences and attitudes towards purchasing local chicken meat. A survey method with a quantitative approach was used in this study. The research was conducted at Caringin Market in Bandung City with the participation of 50 consumers who bought local chicken meat at that location. Data analysis used Chi Square analysis and Fishbein's Multiatribut analysis. The results show that there are differences in consumer preferences for the attributes of local chicken meat. Preferred local chicken meat has a fresh white ‘slightly’ yellowish colour, tender texture, fresh condition, meat free from feather buds, and has a fresh aroma typical of chicken meat. The attributes of local chicken meat from most considered to least considered are freshness, aroma, colour, cleanliness, and texture of the meat, respectively. Respondents' level of liking and attitude assessment showed “Like” and “Very Good”.